Amores exilados: revelações sobre a sexualidade enclausurada - Zaranza, Janaína Sampaio (2004)
This dissertation aims at understanding affective relations that women develop within a space in which they are denied liberty; having as its dominant theme the intimate visit (a benefit conferred the inmate to receive someone on an affective or sexual visit). It is explained how the game of sexual interests is developed within prison’s daily activities involving women with their male and female partners (dealing as well with homoaffective and bisexual relations), people which live not only within but outside the jail, compounding in this way the concept of “Intimate Visit” and demonstrating how this practice is constructed in order to help female inmates lead a sexual life, relating with a male or female partner and maintaining bonds with their families. Besides affective and familiar relations, other types of relations are considered in this work in respect to the complexity of life within prison walls including relations with social agents and policemen. Therefore, it is also considered the role of those social agents as characters who populated as a whole the prison’s universe and whose postures, decisions and actions investigated during the field research are important to the analysis.